2003
DOI: 10.1183/09031936.03.00088102
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a quantitative real-time PCR for the detection of respiratory syncytial virus in pulmonary diseases

Abstract: Respiratory syncytial virus (RSV) is known to cause acute lower respiratory tract infections (ARI) in young children and is involved in exacerbation of chronic obstructive pulmonary disease (COPD) in adults. The role of RSV in stable COPD and the viral load in different respiratory diseases has not been investigated to date.The present authors established and evaluated a quantitative TaqMan1 real-time polymerase chain reaction assay specific for RSV subgroup A. Absolute quantification for the determination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 41 publications
4
72
0
5
Order By: Relevance
“…This analytical sensitivity may be insufficient for reliable detection of microbial pathogens, which can be found at lower clinically relevant loads. For example, infections associated with viral loads as low as 100 viruses per ml of respiratory tract sample may be encountered (1,3). A highly sensitive hybridization on a plastic microarray using DNA capture probes spotted onto microfabricated micropillars has been described recently (19).…”
Section: Discussionmentioning
confidence: 99%
“…This analytical sensitivity may be insufficient for reliable detection of microbial pathogens, which can be found at lower clinically relevant loads. For example, infections associated with viral loads as low as 100 viruses per ml of respiratory tract sample may be encountered (1,3). A highly sensitive hybridization on a plastic microarray using DNA capture probes spotted onto microfabricated micropillars has been described recently (19).…”
Section: Discussionmentioning
confidence: 99%
“…RSV RNA has been detected in archived lung tissue from infants who died in summer months, raising the question of viral persistence (30). More compelling, two recent studies of patients with COPD reported detectable RSV RNA in 24 to 28% of respiratory samples, regardless of whether samples were collected during illness or stable periods (17,18). In addition, RSV RNA has also been detected by real-time RT-PCR in 70% of a small group of symptom-free smokers (31).…”
Section: Discussionmentioning
confidence: 99%
“…transcriptase-polymerase chain reaction (RT-PCR) from a high percentage (24-28%) of patients with stable COPD as well as from ill patients experiencing acute exacerbations (17,18). RSV detection was associated with elevated markers of inflammation and typically was at low copy number.…”
mentioning
confidence: 99%
“…Non-quantitative PCR results may also be difficult to interpret, since low numbers of virus that do not signify an infection may be detected, but this problem is largely overcome by real-time PCR. Molecuar methods can also detect several orders of magnitude less than tissue culture methods (Borg et al, 2003).…”
Section: Molecular Methodsmentioning
confidence: 99%